Strategic campaign attention to abortion before and after Dobbs - Mellissa Meisels (Proceedings of the National Academy of Sciences, 2025)
In 2022, the US Supreme Court overturned the constitutional protection of abortion rights established in Roe v. Wade . In doing so, Dobbs v. Jackson Women’s Health Organization moved status quo on abortion policy more into line with the Republican Party’s stance. Subsequent research has documented the decision’s impact on mass political behavior and opinion, yet less is known about its impact on the behavior of political elites. I provide evidence on congressional candidates’ strategic responses to the decision with original data on campaign platforms ( N = 4,703) from election cycles before and after Dobbs . After the decision, Democrats became significantly more likely to campaign on abortion and to do so using unambiguous language, while Republicans increasingly obfuscated their positions on the issue. Pre-post- Dobbs change in partisan divergence in campaign attention to abortion was driven most strongly by candidates in states with abortion bans set to take effect upon overturning of Roe (i.e., trigger laws and/or pre- Roe laws). Importantly, these shifting patterns of campaign attention were not present in other issue domains, consistent with changes in attention to abortion being driven by Dobbs rather than other contemporaneous factors.